1987
DOI: 10.1159/000184374
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous or Intraperitoneal Vancomycin for the Treatment of Continuous Ambulatory Peritoneal Dialysis Associated Gram-Positive Peritonitis?

Abstract: A clinical and pharmacokinetic study was carried out to determine whether an intraperitoneal (IP) loading dose of vancomycin was as effective as an intravenous (IV) load in the treatment of continuous ambulatory peritoneal dialysis (CAPD)-associated gram-positive peritonitis. Each patient continued a 14-day treatment on IP maintenance doses. All cases of peritonitis (10 in each group) were eradicated. Side effects occurred in 3 patients following IV vancomycin and in none following IP vancomycin. Serum and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 7 publications
(7 reference statements)
0
11
0
Order By: Relevance
“…Recent studies examined the pharmacokinetics of intravenous and intraperitoneal vancomycin in patients undergoing CAPO (Bastani et al 1988; Morse et al 1987;Neal & Bailie 1990). Studies have also examined the influence of intraperitoneal loading doses on serum vancomycin concentrations (Bailie et al 1987;Rogge et al 1985). However, the rate of increase in serum concentrations following an intraperitoneal loading dose is unclear and there are few data concerning the prediction of serum concentrations following intraperitoneal loading doses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies examined the pharmacokinetics of intravenous and intraperitoneal vancomycin in patients undergoing CAPO (Bastani et al 1988; Morse et al 1987;Neal & Bailie 1990). Studies have also examined the influence of intraperitoneal loading doses on serum vancomycin concentrations (Bailie et al 1987;Rogge et al 1985). However, the rate of increase in serum concentrations following an intraperitoneal loading dose is unclear and there are few data concerning the prediction of serum concentrations following intraperitoneal loading doses.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it adheres to first-order pharmacokinetics. The serum concentrations attained, however, tend to be variable unless administered on a mg/kg bodyweight basis, as opposed to a standard Ig dose (Bailie et al 1987;Neal & Bailie 1990;Rogge et al 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The characteristics of the included studies are shown in Table 2. A total of 113 patients from the two RCTs published in 1987 and 1990 were included [16,17]. Bailie et al compared IP with IV as the initial antibiotic administration (vancomycin 1 g/body as a loading dose) for PD-related peritonitis.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Bailie et al compared IP with IV as the initial antibiotic administration (vancomycin 1 g/body as a loading dose) for PD-related peritonitis. The patients in both groups were treated with maintenance IP antibiotic administration [16]. Bennett-Jones et al compared IP (vancomycin 20 mg/L + tobramycin 4 mg/L in dialysate) with IV (vancomycin 0.5-1.0 g/body + tobramycin 1.0 mg/kg body weight) as the initial and maintenance antibiotic administration [17] (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…administration, and a variety of different i.p. vancomycin regimens and doses have been advocated (10)(11)(12)(13)(14)(15)(16)(17)(18). In 1993 the Ad Hoc Committee proposed initial therapy for CAPD peritonitis to include vancomycin 2 grams i.p.…”
mentioning
confidence: 99%